Age and sex but not ATP7B genotype effectively influence the clinical phenotype of Wilson disease - Ferenci, Peter; Stremmel, Wolfgang; Pfeiffenberger, Jan; Weiss, Karl Heinz (Hepatology, 2019)
Wilson disease (WD) is an inherited disorder of hepatic copper metabolism with considerable variation in clinical presentations, the most common ones being liver disease and neuropsychiatric disturbances. This study investigated the clinical presentation in relation to mutations in a large cohort of patients with WD. A total of 1,357 patients (702 children, 655 adults; 1,172 index patients, 185 siblings, all with a Leipzig score ≥4, male/female: 679/678) were studied. The age and the symptoms at presentation were used as key phenotypic markers. Index patients were clinically classified as having either hepatic (n = 711) or neurologic disease (n = 461). Seven hundred fifteen (52.7%) patients had a liver biopsy at diagnosis. DNA was sequenced by the Genetic Analyzers ABI Prism 310 (Perkin Elmer) or 3500 (Applied Biosystems). Three hundred ninety-four different mutation combinations were detected. The most frequent mutation was H1069Q (c.3207C>A; allele frequency: 46.9%), followed by P767P-fs (c.2304dupC; 2.85%), P1134P-fs (c.3402delC; 2.8%), and R969Q (c.2755C>T; 2.18%). There was no correlation between mutations and individual clinical manifestation. There was a gender effect in index patients: Hepatic presentation was more common in females (male/female: 328/383) and neurologic presentation in males (259/202; P < 0.001). At diagnosis, 39.5% of children/adolescents (≤18 years) and 58% of adults already had cirrhosis. The presence of cirrhosis did not correlate with the genotype. Conclusion: These findings refine and extend our understanding of the natural history and individual spectrum/manifestations of WD. Initially, there is asymptomatic hepatic involvement, which may progress and become symptomatic. Neurologic symptoms present many years later.